2015
DOI: 10.1590/0103-6440201300093
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Residual Tetrasodium Pyrophosphate Released from Two Different Anticalculus Flosses

Abstract: The aim of this study was to compare the residual content of tetrasodium pyrophosphate released by two different anticalculus dental flosses (Reach PP® -entangled polypropylene floss and Reach NT® -texturized nylon) in the oral cavity. Ten healthy individuals (aged between 18 and 30 years) were enrolled in this randomized crossover clinical investigation. Participants received instructions on daily dental flossing and the interventions were randomly performed in 2 different groups (NT or PP) of five individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…According to previous studies, some dentifrices containing such agents may provide reduction in biofilm formation by approximately 15%. 32,33 MBC values of tested dentifrices revealed that all the test dentifrices had greater effectiveness against S. mutans compared with L. casei. It also revealed that 3 wt% ZnO and an increased concentration of F-nBG directly corresponded to increased bactericidal potential of experimental dentifrices.…”
Section: Discussionmentioning
confidence: 92%
“…According to previous studies, some dentifrices containing such agents may provide reduction in biofilm formation by approximately 15%. 32,33 MBC values of tested dentifrices revealed that all the test dentifrices had greater effectiveness against S. mutans compared with L. casei. It also revealed that 3 wt% ZnO and an increased concentration of F-nBG directly corresponded to increased bactericidal potential of experimental dentifrices.…”
Section: Discussionmentioning
confidence: 92%
“…Various studies show that the addition of excipients such as tetrasodium pyrophosphate podwer, due to its anti-plaque action, only lasts two hours after application (26). In our study we have evaluated the technique itself for the removal of plaque.…”
Section: Discussionmentioning
confidence: 99%